Application of HBM and POD for insulation assessment of oil-paper insulation system with nonlinear properties - Chi, Cheng; Ren, Zhuoxiang; Yang, Fan (European physical journal. Applied physics, 2025)
The oil-paper insulation system of converter transformers operates under periodic composite AC & DC voltages, with its insulation ability determined by permittivity and conductivity. In the assessment of insulation state, the harmonic balance method (HBM) is adopted in electro-quasi-static field problems to consider the harmonic dependence of permittivity. To reduce the computational burden, proper orthogonal decomposition (POD) is incorporated into the HBM scheme to decrease computational complexity, and a sampling method is put forward based on the characteristics of power system harmonics. Additionally, the nonlinear electric field dependence of the conductivity of the oil-paper insulation system is taken into account in the insulation assessment, which is addressed using the fixed-point iteration method in this paper. Finally, a model of a converter transformer is constructed to demonstrate the effectiveness of the HBM-POD approach.